Transformations in Māori Women's Identity: Some Things Change, Some Stay the Same - Houkamau, Carla Anne (Qualitative Research in Psychology, 2011)
While Māori (the indigenous people of New Zealand) retain a strong collective identity, cultural heterogeneity renders traditional conceptualisations of Māori identity increasingly problematic. To demonstrate the diverse ways Māori define and express their own identities, this article reports research that uses life-story interviews to explore personal perceptions of identity among 35 Māori women ages 18–75. Content analysis revealed traditional cultural factors (particularly whānau/family commitment) were important for identity among all participants, although the expression of these factors differed along with age and background. Older women raised in rural communities expressed family commitment through participating in social and economic activities within their own tribal networks. Younger, urbanised Māori expressed their identities by choosing careers which advanced Māori interests, supporting Māori political aspirations, and forming close relationships with other urban Māori. Life-story excerpts are used to illustrate distinct intergenerational differences in expressions of Māori identity as well as descriptions of “Māoriness,” seldom articulated in literature on the topic. The need to expand current paradigms of Māori identity to incorporate the diversity of group members is emphasised.
Keywords: colonisation; ethnic identity; kaumātua; mana wāhine; māori identity; urbanisation